Penerapan Metode Takrir dalam Menghafal Al-Qur’an - Yasin Yusuf (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2020)
Madrasah Ibtidaiyah Hidayatun Najah is an educational institution with a program of memorizing the Qur'an using the takrir method, but some students still have not reached the target according to the provisions. This study uses a qualitative approach. Data collection techniques using interviews, observation, and documents. The results of this study include; (1) Planning for the implementation of the takrir method in memorizing the Qur'an at Madrasah Ibtidaiyah Hidayatun Najah Tuban is the authority of the madrasa head and supervising teachers, students are targeted to memorize 1.5 juz within a year; (2) The implementation of the takrir method in memorizing the Qur'an at Madrasah Ibtidaiyah Hidayatun Najah Tuban following the planning steps; (3) The implementation of the takrir method in memorizing the Qur'an at Madrasah Ibtidaiyah Hidayatun Najah Tuban is very suitable and runs smoothly, but several things need to be evaluated, including a) students only have little time for muroja'ah (repeating). back) previous memorization, b) students forget the verses that have been previously memorized, c) students are still often fooled by almost similar verses, and d) some students have not reached the target according to the provisions